2005
DOI: 10.1158/0008-5472.can-05-0765
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Metronomic Combined with Intermittent Bolus-dose Cyclophosphamide Is an Effective Long-term Chemotherapy Treatment Strategy

Abstract: Metronomic chemotherapy refers to the close, regular administration of comparatively low doses of cytotoxic drugs, with minimal or no drug-free breaks, over prolonged periods. It is thought to have an antiangiogenic basis. However, whereas surprisingly durable and potent tumor responses have been observed in a number of preclinical tumor models, relapses usually eventually occur using this type of treatment strategy. We therefore decided to test modified metronomic chemotherapy regimens that might significantl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 21 publications
5
97
0
Order By: Relevance
“…Metronomic administration (20 mg/kg/d) of cyclophosphamide was carried out by addition of the drug to the drinking water as originally described (10), and later modified (14) by the addition of an upfront i.p. bolus dose (150 mg/kg).…”
Section: Derivation Of Metastatically Competent Sublinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metronomic administration (20 mg/kg/d) of cyclophosphamide was carried out by addition of the drug to the drinking water as originally described (10), and later modified (14) by the addition of an upfront i.p. bolus dose (150 mg/kg).…”
Section: Derivation Of Metastatically Competent Sublinesmentioning
confidence: 99%
“…These were treated with control PBS i.p., or administered a bolus plus oral low-dose metronomic cyclophosphamide regimen (as described in ref. 14), or given DC101 i.p. (15).…”
Section: B-hcg Monitoring Of B16 Melanoma Experimental Metastases In mentioning
confidence: 99%
“…Metronomic chemotherapy is defined as regular administration of a chemotherapeutic drug at relatively low (nontoxic) doses, over prolonged periods, with no extended drug-free break periods [63]. Using different preclinical breast cancer models, several studies showed a strong relationship between decreased number of circulating EPC and efficiency of various metronomic chemotherapy regimens [65][66][67][68]. These studies demonstrated that EPC can be used successfully as a surrogate marker in mice for determining the optimal biological dose for various metronomic chemotherapies, thus avoiding empiricism (at least in mice), with respect to determining the optimal biological dose in metronomic chemotherapy regimens.…”
Section: Clinical Applications: Epc As Biomarker and Therapeutic Target?mentioning
confidence: 99%
“…MTD chemotherapy would debulk the tumour before the initiation of MET, which would then have an anti-angiogenic effect, while abolishing the endothelial cell rebound. 6 The concepts of combining MET with MTD chemotherapy or with agents targeting vascular endothelial growth factor …”
mentioning
confidence: 99%
“…MTD chemotherapy would debulk the tumour before the initiation of MET, which would then have an anti-angiogenic effect, while abolishing the endothelial cell rebound. 6 The concepts of combining MET with MTD chemotherapy or with agents targeting vascular endothelial growth factor (VEGF) and platelet-derived growth factor receptors were brought together in a single pre-clinical study reported by Pietras and Hanahan. 7 In this article, we generalise this chemo-switch (C-S) concept to other tumour models and other drugs, evaluating its effects on angiogenesis and cancer stem cell (CSC) number.…”
mentioning
confidence: 99%